The social solidarity economy as agent of economic activation in times of the COVID-19 pandemic - Binns-Hernández, Henry (2022)
The purpose of emerging economies such as social solidarity and collaborative, seek through entrepreneurship, to achieve a social focus, providing different sources of employment, marketing of goods and services at a fair price, eliminating intermediation in the chain of production; allowing to generate value and competitive advantages of which were not counted in the past. The models of the economies of the countries are in constant change and adaptation to the new needs of the different populations, it is here where a series of economies emerge, whose aim pursues a spirit of solidarity in favor of the benefit first of the people and later of the profit. The collaborative economy initiatives and the social solidarity economy are two of the new and emerging models of economies that countries are adopting, with the aim of reaching vulnerable populations and sometimes confined to oblivion by government agents. The rebound in poverty and unemployment rates in countries around the world, aggravated by COVID-19, will translate into an increase in the crime rate, as well as business closures. It is here where the incentive by the government authorities through financing and the participating actors play an important role in the generation of new business models that lead to new ventures associated with reinvention and linkages in national economies that serve as agents. of economic activation.